Triton-B Mediated Efficient Synthesis of Thioxoimidazolidine-4,5-diones - Kishore1, Ram; Kamboj1, M.; Shukla2, M.; Chaturvedi3, Devdutt (Asian Journal of Chemistry, 2019)
A simple, mild and efficient protocol for the synthesis of thioxoimidazolidine-4,5-diones (1-15) from substituted thiourea employing Triton-B/CS2 system has been discussed. The protocol described is an easy, efficient, nature-friendly method using cheap, easily available, less toxic reagents at room temperature. The synthesis involves the reaction between substituted thiourea in toluene and oxalyl chloride at room temperature using phase transfer catalyst Triton-B/CS2 system.